2023
DOI: 10.1159/000533587
|View full text |Cite
|
Sign up to set email alerts
|

Association of Epidermal Biophysical Properties with Obesity and Its Implications

Tingting Zhu,
Shuyun Yang,
Theodora M. Mauro
et al.

Abstract: <b><i>Background:</i></b> Obesity is a condition defined by an excess amount of body fat, with body mass index (BMI) of 30 and higher. It is associated with a number of other medical conditions, including insulin resistance, diabetes mellitus, and cardiovascular diseases, as well as dyslipidemia, and it is also associated with several cutaneous disorders such as atopic dermatitis, psoriasis, intertriginous dermatitis, acanthosis nigricans and skin infections. <b><i>Summary:&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 102 publications
0
1
0
Order By: Relevance
“…Previous studies showed that compromised epidermal function can increase and/or exacerbate cutaneous inflammation, while cutaneous inflammation can result in systemic inflammation. 117,118 Because of the pathogenic role of inflammation in diabetes mellitus, approaches that improve epidermal function, including epidermal permeability barrier, stratum corneum hydration and skin surface pH, can possibly attenuate diabetes mellitus. 116 The beneficial effects of T1DM on AD have been demonstrated in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that compromised epidermal function can increase and/or exacerbate cutaneous inflammation, while cutaneous inflammation can result in systemic inflammation. 117,118 Because of the pathogenic role of inflammation in diabetes mellitus, approaches that improve epidermal function, including epidermal permeability barrier, stratum corneum hydration and skin surface pH, can possibly attenuate diabetes mellitus. 116 The beneficial effects of T1DM on AD have been demonstrated in several studies.…”
Section: Discussionmentioning
confidence: 99%